2019
DOI: 10.3136/fstr.25.257
|View full text |Cite
|
Sign up to set email alerts
|

<i>Thymbra capitata</i> Essential Oil Use to Preserve Physicochemical and Microbiological Qualities of Pomegranate Juice

Abstract: This work studied the possible use of Thymbra capitata essential oil in the preservation of pomegranate juice qualities. We monitored the effect of the oil on the physicochemical and microbiological qualities of the juice during 245 days of storage at 5 and 20 ℃. Treated juices showed slight decrease of pH, total sugars and phenolic contents after 245 days of storage. Additionally, the essential oil had a significant effect on the juice microbiological quality and caused a decrease of bacterial count after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The interaction of antimicrobial compounds with food matrix components also limits their application in food products [13,17,21,[26][27][28][29][30]. Certain nutrients in food can have a protective effect on microorganisms; therefore, it would be necessary to use higher concentrations of natural antimicrobials.…”
Section: Using Natural Antimicrobials In Fruit-derived Foodsmentioning
confidence: 99%
“…The interaction of antimicrobial compounds with food matrix components also limits their application in food products [13,17,21,[26][27][28][29][30]. Certain nutrients in food can have a protective effect on microorganisms; therefore, it would be necessary to use higher concentrations of natural antimicrobials.…”
Section: Using Natural Antimicrobials In Fruit-derived Foodsmentioning
confidence: 99%
“…Moreover, an intense antibacterial activity of Origanum compactum essential against Escherichia coli K12 and Bacillus subtilis 6633 were shown by Bouyahyaet al 13 . On the other hand, Charfiet al 14 have also demonstrated that essential oil of Thymbra capitata had a significant antimicrobial effect on pomegranate juice natural flora (aerobic mesophilic bacteria, Streptococcus thermophilus, yeasts, and molds) allowing the preservation of the quality of the juice.…”
Section: Introductionmentioning
confidence: 99%